Conference Proceedings. 2nd International IEEE EMBS Conference on Neural Engineering, 2005.
DOI: 10.1109/cne.2005.1419667
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Position Sensing: A Machine Vision Approach

Abstract: -Numerous approaches to sensing limb position for controlling neural prostheses have been proposed, evaluated and even incorporated into commercial products. In general, these technologies have focused on the goals of accuracy, convenience and cost. Here we propose an approach to sensing upper limb posture for a stroke rehabilitation system that does not require any devices attached to the subject. This is achieved through the use of a machine vision approach, which involves focusing a digital video camera on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…A more cost affective solution such as using webcam and off-the-shelf RGB-D cameras such as Kinect [ 117 ] outlines the problem in model fidelity [ 118 ], difficulty to assess distal segments [ 119 ] including the hand [ 120 , 121 ], large static error when benchmarked with commercial motion capture [ 122 , 123 ] and false detection of trunk rotation for compensatory movement [ 124 ]. Chen et al [ 125 ] in their survey of depth imagery concluded that the higher resolution body part modelling is required for further research to improve the distal recognition challenges in human action recognition.…”
Section: Discussionmentioning
confidence: 99%
“…A more cost affective solution such as using webcam and off-the-shelf RGB-D cameras such as Kinect [ 117 ] outlines the problem in model fidelity [ 118 ], difficulty to assess distal segments [ 119 ] including the hand [ 120 , 121 ], large static error when benchmarked with commercial motion capture [ 122 , 123 ] and false detection of trunk rotation for compensatory movement [ 124 ]. Chen et al [ 125 ] in their survey of depth imagery concluded that the higher resolution body part modelling is required for further research to improve the distal recognition challenges in human action recognition.…”
Section: Discussionmentioning
confidence: 99%
“…user interface along with sensor information display [5] is implemented to provide feedbacks to the patient as well as provide observatory to the therapist. All information such as sensor data, recognized activities, medical records, etc are resided in central repository using relational database.…”
Section: Figure 2 Physical Therapy Management System Operationsmentioning
confidence: 99%
“…With advances in sensing, intelligence, networking and communication technologies, several tele-rehabilitation systems were proposed [2,3,4,5]. Kousidou et al [2] developed roboticbased shaping therapy to regain daily motor activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, to minimize the inconvenience and cost of commuting, with home rehabilitation, the patient is allowed to perform rehabilitation activities in comfortable conditions offered by their own home. All this contributes on the one hand to improve the quality of treatment and speed up recovery (Maclean et al, 2002) and on the other hand, reduces hospitalizations and consequently, the costs of the health care system (Han et al, 2005).…”
Section: Introductionmentioning
confidence: 99%